The Best Book About Pessimism I Ever Read. - McKenzie, Lucy; Mulholland, Neil; Kusel, Andrea; Grässlin, Karola (Braunschweig : Kunstverein Braunschweig, 2002)
Mckenzie, Lucy ; Byrne, John ; Camplin, Bonnie ; David, Enrico ; Farquhar, Keith ; Gray, Alasdair ; Heeps, Ronnie ; Olowska, paulina ; Rosier, mathilde ; Skaer, Lucy ; Tatham Joanne ; O'Sullivan, Tom
The best Book About Pessimism i Ever Read, Kunstverein Braunschweig, Braunschweig, 22 juni tot 25 augustus 2002
boek